2001
DOI: 10.1099/00221287-147-6-1461
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux in cellulose batch and cellulose-fed continuous cultures of Clostridium cellulolyticum in response to acidic environment

Abstract: Clostridium cellulolyticum, a nonruminal cellulolytic mesophilic bacterium, was grown in batch and continuous cultures on cellulose using a chemically defined medium. In batch culture with unregulated pH, less cellulose degradation and higher accumulation of soluble glucides were obtained compared to a culture with the pH controlled at 72. The gain in cellulose degradation achieved with pH control was offset by catabolite production rather than soluble sugar accumulation. The pH-controlled condition improved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
5
32
0
Order By: Relevance
“…Growth on cellulose or straw differs from that on soluble sugars by several factors: (a) the necessity for bacteria first to adhere to the substrate and second to degrade it, (b) different growth rate, (c) different physiological state of the bacteria; the carbon flow is consequently different in cellulose and/or wheat straw grown cells. The metabolism of another anaerobic cellulolytic bacterium Clostridium cellulolyticum was studied in details in batch and continuous cultures on cellobiose or cellulose, and a modification of metabolic fluxes was also observed between the two substrates (Desvaux et al 2000;Desvaux et al 2001). Accumulation of phosphorylated sugars in the extracellular medium of growing bacteria (present work) but also of resting cells (Nouaille et al 2004) is quite surprising.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Growth on cellulose or straw differs from that on soluble sugars by several factors: (a) the necessity for bacteria first to adhere to the substrate and second to degrade it, (b) different growth rate, (c) different physiological state of the bacteria; the carbon flow is consequently different in cellulose and/or wheat straw grown cells. The metabolism of another anaerobic cellulolytic bacterium Clostridium cellulolyticum was studied in details in batch and continuous cultures on cellobiose or cellulose, and a modification of metabolic fluxes was also observed between the two substrates (Desvaux et al 2000;Desvaux et al 2001). Accumulation of phosphorylated sugars in the extracellular medium of growing bacteria (present work) but also of resting cells (Nouaille et al 2004) is quite surprising.…”
Section: Discussionmentioning
confidence: 70%
“…For example, there could be a need of more energy in the first hours of growth on solid substrate for induction of synthesis of specific proteins involved in adhesion (Roger et al 1990) or cellulolysis (Béra-Maillet et al 2000). In addition, acetate and succinate production may be affected differently by several factors such as pH, as shown previously on continuous cultures of S85 (Weimer 1993) or on other bacteria (Desvaux 2001). As F. succinogenes also produces formate as a minor metabolite (Miller 1978;Matheron et al 1997), it would have been interesting to monitor its concentration during the growth on the two substrates to see the evolution of its production with time.…”
Section: Discussionmentioning
confidence: 95%
“…Corresponding to the accumulation of sol- uble sugars under high initial cellulose concentrations, lactate was produced by the coculture. In fact, it was found that lactate was produced by Clostridium cellulolyticum (28) and C. thermocellum ATCC 27405 (29) with an increase in initial cellulose concentrations. Therefore, initial cellulose concentrations might play a role in influencing metabolism pathways in fermentative thermophilic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…A longer-term option being considered is the production of molecular hydrogen from biomass using fermentative, anaerobic microorganisms (38). For example, many mesophilic Clostridium and Enterobacter species can grow on fermentable sugars and produce hydrogen as a by-product of energy metabolism (8,11,16,28,38).Studies suggest that biohydrogen production rates may be enhanced at higher temperatures (9, 23). In fact, the production and consumption of molecular hydrogen drive the microbial physiology and bioenergetics of many hyperthermophilic bacteria and archaea inhabiting hydrothermal environments (1).…”
mentioning
confidence: 99%